The Management of Reputational Risks in Banks: Findings From Germany and Switzerland. (July 2019) - Zaby, Simon; Pohl, Michael
This article identifies reputation-risk-relevant factors for banks, and the focus will be placed on the development of an indicator-based model for the assessment of reputation. Requirements and insights are based on a survey of credit institutions in Germany and Switzerland, which have been predominantly affected during the financial crisis by aptly nascent risks and which are thereby also partially affected even today. Reputation level can be considered as a temporally dynamical phenomenon which predominantly develops depending on the changes in the reputation drivers and expectations of the groups of stakeholders. This control parameter can be determined with the aid of Reputation Index Points (RIP). Efficient reputation risk management can, in the future, help prevent negative spillover effects from banks which face difficulties from the society or the taxpayers.